Assessing the Role of Price and Service Quality in Influencing Customer Decisions at K24 Wahid Hasyim Pharmacy, Palembang - Al hady, M. Ridho; Darwin, Darwin; Syakina, Bella (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
In the competitive business landscape, effective marketing strategies are crucial, especially in the resilient and growing pharmacy industry. This study examines how price and service quality affect consumer purchasing decisions at K24 Pharmacy on Jl. KH Wahid Hasyim Palembang. Given the Indonesian pharmacy sector's rapid growth, particularly during the COVID-19 pandemic, understanding consumer behavior is essential. Despite K24 Pharmacy's competitive advantages, it faces significant competition. The study aims to determine the impact of price and service quality on consumer decisions at K24 Pharmacy, offering strategic insights for improvement. Conducted from April to May 2024, this quantitative research surveyed 100 customers using a structured questionnaire. Data analysis involved descriptive statistics and multiple regression analysis using SPSS software to evaluate the influence of price and service quality on purchasing decisions. Findings reveal that service quality significantly affects purchasing decisions, while price does not have a statistically significant impact. The reliability test showed high internal consistency for both variables and normality and multicollinearity tests confirmed data suitability for regression analysis. Service quality, including reliability, responsiveness, assurance, empathy, and physical evidence, has a significant positive relationship with purchasing decisions. Conversely, price factors like affordability, quality alignment, and competitiveness did not significantly influence consumer choices. K24 Pharmacy should focus on enhancing service quality to boost consumer satisfaction and loyalty. While maintaining competitive pricing, the emphasis should be on improving service aspects, which more substantially impact purchasing decisions. In conclusion, the research underscores the critical role of service quality in consumer decision-making at K24 Pharmacy, providing strategic insights for sustaining and enhancing its market position.